Drug Resistance in Toxoplasma gondii - Montazeri, Mahbobeh; Mehrzadi, Saeed; Sharif, Mehdi; Sarvi, Shahabeddin; Tanzifi, Asal; Aghayan, Sargis A.; Daryani, Ahmad (Frontiers in Microbiology, 2018)
Toxoplasma gondii (T. gondii) is a global protozoan parasite infecting up to one-third of the world population. Pyrimethamine (PYR) and sulfadiazine (SDZ) are the most widely used drugs for treatment of toxoplasmosis; however, several failure cases have been recorded as well; suggesting the existence of drug resistant strains. This review aims to give a systematic and comprehensive understanding of drug resistance in T. gondii including mechanisms of resistance and sites of drug action in parasite. Analogous amino acid substitutions in the Toxoplasma enzyme were identified to confer PYR resistance. Moreover, resistance to clindamycin, spiramycin, and azithromycin is encoded in the rRNA genes of T. gondii. However, T. gondii SDZ resistance mechanism has not been proved yet. Recently there has been a slight increase in SDZ resistance. That is why the majority of studies were carried out using SDZ. Six strains resistant to SDZ were found in clinical cases between 2013 and 2017 which among Brazilian T. gondii isolates, TgCTBr11, Ck3, and Pg1 were identified in human toxoplasmosis, as well as in livestock intended for human consumption. In conclusion, recent experimental studies in clinical cases have clearly shown that drug resistance in Toxoplasma is ongoing. Thus, establishing a more effective therapeutic scheme in the treatment of toxoplasmosis is critically needed. The emergence of T. gondii strains resistant to current drugs, reviewed here, represents a concern not only for treatment failure but also for increased clinical severity in immunocompromised patients. To improve the therapeutic outcome in patients, a greater understanding of the exact mechanisms of drug resistance in T. gondii should be developed. Thus, monitoring the presence of resistant parasites, in food products, would seem a prudent public health program.